2016
DOI: 10.1002/tcr.201600088
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Base Catalyzed Stereo‐ and Regioselective Bromocyclization

Abstract: Oxygen- and nitrogen-containing heterocyclic compounds are widely recognized as key components in many natural products and biologically relevant molecules, but often the problem comes down to methodologies in synthesizing them. Halocyclization of olefinic substrates is a promising strategy in the construction of O- and N-heterocyclic compounds, which further signifies the development of their asymmetric variants. Over the past years, our group has been devoted to this particular area of asymmetric electrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…We believe the systematic evidence and specific findings described herein not only provides new mechanistic guidance in understanding haloaddition and halocyclization reactions of alkenes and alkynes, especially those catalyzed by quinuclidine‐bearing cinchona alkaloids as illustrated by the groups of Yeung , Tang , Henneke , Denmark , Ishihara , Yamamoto and others, [33–42,61–78] but also provides fundamental knowledge in expanding halogen bond‐based reactions in synthesis, particularly concerning iodine‐based reagents and amine catalysis. Wider implications of the current work to chalcogen‐ and pnictogen‐based Lewis acids, which similarly feature sigma‐hole acceptor capabilities, is an intriguing proposition and represents a growing field of applications in catalysis, anion‐transport and may even be considered a less ‘unorthodox’ approach to the design of new reactions and methods in the future [79–84] …”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We believe the systematic evidence and specific findings described herein not only provides new mechanistic guidance in understanding haloaddition and halocyclization reactions of alkenes and alkynes, especially those catalyzed by quinuclidine‐bearing cinchona alkaloids as illustrated by the groups of Yeung , Tang , Henneke , Denmark , Ishihara , Yamamoto and others, [33–42,61–78] but also provides fundamental knowledge in expanding halogen bond‐based reactions in synthesis, particularly concerning iodine‐based reagents and amine catalysis. Wider implications of the current work to chalcogen‐ and pnictogen‐based Lewis acids, which similarly feature sigma‐hole acceptor capabilities, is an intriguing proposition and represents a growing field of applications in catalysis, anion‐transport and may even be considered a less ‘unorthodox’ approach to the design of new reactions and methods in the future [79–84] …”
Section: Discussionmentioning
confidence: 64%
“…Indeed, we became intrigued by the halogen bonding nature of the electrophilic reagents NIS and NBS that are commonly used in catalytic halo‐functionalizations, specifically their mechanistic role and reactivity in the halo‐cyclization of γ‐olefinic alcohols and acids in the presence of amine catalysts ( Scheme 1). [31–42] For instance, according to literature reports, NIS and NBS are one of the most common reagents used to oxidize N−H bonds to N−X bonds [43] . Indeed, it is reported that primary and secondary amines are readily oxidized by NIS to give N ‐iodo amines, [44] while secondary amines are readily oxidized by NBS to generate N ‐bromo amines ( Scheme 1 ,A , equation 1 ) [45] .…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric electrophilic halocyclization, especially halolactonization, has acquired tremendous importance in recent years because of its wide applications in organic and medicinal chemistry . In the past decade, significant efforts were devoted to the catalytic asymmetric synthesis of five- and six-membered halolactones. In sharp contrast, catalytic enantioselective protocols for the synthesis of enantioenriched medium-sized rings such as seven- and eight-membered halolactones are still uncommon, despite their usefulness in the synthesis of biologically active molecules …”
mentioning
confidence: 99%
“…The electrophilic halocyclization of alkenes has emerged as an unparalleled platform for the efficient assembling of cyclic compounds via introducing a new halogen group and creating a new ring. In this context, considerable research efforts have been paid to the halocyclization of olefinic 1,3-dicarbonyls and olefinic amides. Nonetheless, from an eco-friendly and practical point of view, these significant achievements are still plagued by some disadvantages, such as the use of catalysts, the necessity of bases or oxidants, and the need for high reaction temperature or toxic organic solvents. In continuation of our research interest in the cyclization reaction, as well as reactions in aqueous media, we recently have found that treatment of olefinic 1,3-dicarbonyls or olefinic amides with halogen sources in aqueous media open to the air at room temperature could realize the synthesis of 2,3-dihydrofurans or benzoxazines (Scheme ).…”
Section: Introductionmentioning
confidence: 99%